Epibionts of an Introduced King Crab in the Barents Sea: A Second Five-Year Study. - Dvoretsky, A.G. & V.G. Dvoretsky (Diversity-Basel, 2023)
The biodiversity, infestation patterns, and spatial distribution of organisms living in association with the introduced red king crab Paralithodes camtschaticus were studied in Dalnezelenetskaya Bay, southern Barents Sea, in 2009-20013 to update a list of species, reveal long-term changes in this epibiotic community, and identify key factors affecting the prevalence and intensity of infestation. A total of 90 associated species were found throughout the study period, or twice as many as in 2004-2008, reflecting relatively low similarity between these periods. Half of the species were found on one to three crabs only. Copepods had the maximum diversity (23 species). For the first time, macroalgae were found as epibionts of red king crabs. Overall, the highest prevalences were found for the amphipod Ischyrocerus commensalis (74.2%), the copepods Tisbe furcata (57.7%) and Harpacticus uniremis (29.4%), the amphipod Ischyrocerus anguipes (27.3%), and the fish leech Johanssonia arctica (16.2%). Redundancy analysis showed that host size was the most important driver of species abundance, followed by shell condition, water temperatures in the coastal Barents Sea in May and June, and sex. These factors, coupled with the range expansion of red king crabs and climate changes in the Barents Sea, provide good explanations for the differences between the 2004-2008 and 2009-2013 fouling communities. Distribution patterns for common taxa on the host reflect larval settlement patterns and/or relationships between the host and associated species. These results expand our knowledge of infestation patterns for the invasive red king crab and provide a reference point for further monitoring.